Development of vanilla flavored coffee drink in can - Palma, Gale T.; Francisco, Ma. Leonora dL. (1999.)
This study was aimed to develop vanilla-flavored coffee in can. The study involved formulation of the vanilla-flavored coffee drink, thermal processing, verification of the thermal process, and consumer acceptability of the final product. A preliminary study was conducted to choose between samples prepared with refined sugar and samples with brown sugar. Results of the data analysis showed no significant difference between samples. Coffee prepared with brown sugar was chosen not only because of the lower cost, but also because brown sugar enhanced the appearance, aroma and strength of the coffee flavor. The formulation of vanilla-flavored coffee drink focused on the selection of the type of vanilla flavoring ideal for the product. The sensory evaluation did not show any significant difference between the sample prepared with liquid flavoring and with crystallized vanilla. Vanilla flavoring in syrup form was chosen based on availability. The thermal processing of vanilla-flavored coffee at 250F for 20 minutes produced an F value of 19.22 minutes. This value exceeded the F value of the reference organism which was 7.5 minutes. Verification of the thermal process by physico-chemical tests, can examination and microbiological examination indicated the integrity of the product. Sensory evaluation for the consumer acceptability of the final product showed favorable responses. The vanilla-flavored coffee was described as moderately sweet, moderately brown in color, with distinct aroma and just the right degree of bitterness and vanilla flavor. Majority of the panelists stated that they liked the product and would drink it frequently.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coffee; Beverages